The impact of personality traits on enhanced academic self-efficacy and teaching innovation behavior among vocational teachers in China - Zhang, Miao; Anyanwu, Clinton Chidiebere; Liu, Yaoping; Junaidi, Junaidi (Journal of Asian Scientific Research, 2025)
This study aims to investigate how personality trait dimensions influence teachers’ academic self-efficacy and teaching innovation behavior. A total of 635 teachers from vocational schools in China participated by filling out a comprehensive questionnaire designed to assess various personality traits and their impact on teaching practices. Structural equation modeling (SEM) was employed to examine the research hypotheses. The findings revealed that teachers’ personality trait dimensions, such as agreeableness, extraversion, neuroticism, and openness, have a positive and significant effect on teachers’ academic self-efficacy. In contrast, conscientiousness did not demonstrate a significant role in influencing teachers’ self-efficacy, suggesting that not all personality traits contribute equally to teachers' confidence in enhancing academic abilities. The findings reveal that academic self-efficacy partially mediates the relationship between teachers' personality traits and their teaching innovation behavior. This indicates that while personality traits can directly influence teaching practices, the level of self-efficacy also plays a crucial role in this dynamic. Education stakeholders should foster attractive collaborations between teachers and students, particularly by addressing teachers’ personal psychological needs during the learning process. However, this study was limited to vocational teachers in China, suggesting the need for future research to explore cross-regional cultures, various educational departments, and different religious contexts to gain a more comprehensive understanding of these relationships.